2017
DOI: 10.1177/0333102417731777
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between migraine and rosacea: Systematic review and meta-analysis

Abstract: Objective To systematically review the association between migraine and rosacea. Background Migraine is a complex disorder with episodes of headache, nausea, photo- and phonophobia. Rosacea is an inflammatory skin condition with flushing, erythema, telangiectasia, papules, and pustules. Both are chronic disorders with exacerbations of symptoms almost exclusively in areas innervated by the trigeminal nerve. Previous studies found an association between these disorders. We review these findings, provide a meta-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 96 publications
2
31
1
2
Order By: Relevance
“…A population-based study conducted in the United Kingdom observed a significant association between rosacea and migraine in females (OR: 1.22; 95% CI: 1.16–1.29) [ 10 ]. The most recent systematic review and meta-analysis also reported the possible association between the development of migraine and rosacea [ 35 ].…”
Section: The Risk Of Neurologic Diseases In Rosaceamentioning
confidence: 99%
“…A population-based study conducted in the United Kingdom observed a significant association between rosacea and migraine in females (OR: 1.22; 95% CI: 1.16–1.29) [ 10 ]. The most recent systematic review and meta-analysis also reported the possible association between the development of migraine and rosacea [ 35 ].…”
Section: The Risk Of Neurologic Diseases In Rosaceamentioning
confidence: 99%
“…The connection between migraine and sleep disorders has been recognized [35,36]. However, the connection of migraine and rosacea and other skin disorders is only beginning to emerge, and studies have mainly focused on the increase in odds ratio of migraine in patients with rosacea, not the other way around [37,38]. There are potential pathophysiological overlaps with migraine and neuroendocrineimmune-related skin disorders, in which also calcitonin gene related peptide (CGRP) has been suggested to play a role.…”
Section: Increased Comorbidity Based On Phenotypic Disease Networkmentioning
confidence: 99%
“…Migraine has repeatedly been associated with rosacea. 1 Both are chronic inflammatory conditions with relapsing episodes of headache for migraine, and redness/flushing and/ or papules/pustules for rosacea. Relapses may be triggered by various endogenous and/or exogenous factors such as different foods and drinks, exercise, sun/UV exposure, heat and stress.…”
Section: Introductionmentioning
confidence: 99%
“…10 Common demography, triggers and associated neuropeptides suggest a shared pathophysiological pathway. 1 Despite overwhelming evidence of a connection between migraine and rosacea, [15][16][17][18][19][20] underdiagnosis in both disorders must be considered as a confounder in previous research, and a systematic approach is therefore needed to confirm this connection and to better characterise exact overlap between these diseases. Establishment of prospective patient cohorts with a physiciandiagnosis of either migraine or rosacea will help confirm this connection and uncover possible risk factors and comorbidities in both.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation